Dante as political theorist reading monarchia - Ardizzone, Maria Luisa (Cambridge Scholars Publishing, 2018)
Dante's Latin treatise Monarchia inscribes itself within the long medieval conflict between Pope and Emperor and the debate that opposed the theorists of theocracy to the supporters of the empire. The Monarchia, traditionally assumed to be a subversive work as its tormented reception testifies - it remained listed in the Index of Prohibited Books from 1559 to the end of the 19th century - results from the strong connection Dante emphasized between politics and ethics. The bene esse of human beings is the crucial issue that the treatise discusses since its very beginning. More than focusing on.